The in silico study of the COBRA gene family in sugarcane related to potential biomass content - Riza Arief PUTRANTO; Galuh Wening PERMATASARI; Rizka Tamania SAPTARI (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2022)
AbstractSugarcane (Saccharum sp.) is potential as a biofuel and biomaterial source for its high cellulose content. Cellulose is the main constituent of the plant cell wall, as a linear chain arranged in a polysaccharide bundle, called cellulose microfibril. A gene named COBRA has been revealed to play role in the orientation of microfibril and cellulose crystallization. The COBRA gene in the Saccharum spp is under-explored. Therefore, the in silico study was conducted to explore the COBRA gene in Saccharum sp. By comparative genomics methods, the COBRA genes from Arabidopsis sp. (AtCOBLs) were compared to the Saccharum sp. (SoCOBLs). The conserved domain was then identified and the cluster system was constructed under a phylogenetic tree. Furthermore, each SoCOBLs protein was modelled to analyze its structure. According to the analysis, eleven of Saccharum sp. genomic scaffolds were successfully identified. Moreover, conserved domain identification resulted in nine SoCOBLs proteins. The phylogenetic tree showed two main clusters: I and II, differentiating those COBLs families based on the protein sequence, domain motif and amino acid properties. It leads to the variation of SoCOBLs protein structure as the results of the amino acid properties. Overall, the COBRA gene has been identified genomically in Saccharum sp. Yet, the function and tissue-specific expression are still unclear. It was predicted to act as the regulator of microfibril orientation and the cellulose synthesis process. Hence, further analyses by in vitro and in vivo are indispensable.[Keywords: cellulose, comparative genomic, Saccharum sp.]AbstrakTanaman tebu (Saccharum sp.) berpotensi sebagai sumber bahan bakar nabati dan biomaterial karena kandungan selulosanya yang tinggi. Selulosa merupakan komponen utama penyusun dinding sel tanaman, sebagai rantai lurus yang tersusun dalam gugusan polisakarida, yang disebut mikrofibril selulosa. Sebuah gen bernama COBRA telah diketahui berperan dalam menentukan arah mikrofibril dan kristalisasi selulosa. Gen COBRA pada spesies Saccharum spp. belum banyak dipelajari. Oleh karena itu, kajian in silico dilakukan untuk mempelajari gen COBRA pada Saccharum sp. Melalui metode perbandingan genomika, gen COBRA dari Arabidopsis sp. (AtCOBLs) dibandingkan dengan gen COBRA dari Saccharum sp. (SoCOBLs). Domain conserve pada gen kemudian diidentifikasi dan sistem klaster disusun dalam sebuah pohon filogeni. Setelah itu, dibuat model untuk menganalisis struktur dari protein SoCOBL. Dari hasil analisis, sebelas perancah genom Saccharum sp. berhasil diidentifikasi. Kemudian, identifikasi daerah lestari menghasilkan sembilan protein SoCOBL. Pohon filogeni menggambarkan dua klaster utama: I dan II, yang membedakan famili SoCOBLs tersebut berdasarkan sekuens protein, motif domain, dan karakteristik asam amino. Karakteristik asam amino menyebabkan variasi pada struktur protein-protein SoCOBL. Secara umum, gen COBRA telah teridentifikasi pada Saccharum sp., meskipun fungsi dan ekspresi spesifiknya pada jaringan masih belum diketahui. Diperkirakan gen tersebut berperan sebagai pengatur arah mikrofibril dan proses sintesis selulosa. Oleh karena itu, perlu adanya analisis lebih lanjut pada level in vitro dan in vivo.[Kata kunci: selulosa, genomika komparatif, Saccharum sp.]